Employee Health Screening and Well-Being Assessment to Support Organizational Performance in an Academic Workplace - Imam Tri Sutrisno; Rafika Rosyda; Dedah Ningrum; Diding Kelana Setiadi; Amanda Puspanditaning Sejati (Jurnal Pengabdian Masyarakat Lentora, 2026)
Introduction: This community service project was conducted through a collaborative partnership between the nursing program and the UPI Sumedang Campus administration. The activity aimed (1) to assess the health profile and identify risk factors for NCDs among UPI Campus employees in Sumedang, most of whom have sedentary work patterns, and (2) to utilize these findings as a basis for initiating and advocating targeted, evidence-based workplace health promotion and wellness interventions. Methods: Employees were engaged through preliminary informational sessions coordinated with campus representatives to explain the purpose and procedures of the program and to encourage voluntary participation. The methods included comprehensive health screening—comprising measurements of blood pressure, blood glucose, cholesterol levels, body mass index, and body composition—alongside structured lifestyle interviews. The collected data were analyzed to identify health risks and to inform the development of context-specific recommendations for workplace health promotion. Results: Screening of 44 participants revealed a high burden of NCDs risk factors, including pre-hypertension (40.9%), hypertension (25%), overweight (50%), obesity (25%), and high to very high visceral fat (75%). Low skeletal muscle mass was observed in 86.4% of participants, while pre-diabetes and hyperuricemia were identified in 13.6% and 38.6%, respectively, indicating an elevated risk of metabolic syndrome and future cardiovascular disease. Participation reached 73% (44 of 60 invited employees). Lifestyle interviews and feedback sessions identified limited time, and prolonged sedentary work as key barriers to healthy behavior, while discussions generated interest in workplace physical activity initiatives and healthier food options. Conclusion: The conclusion of this activity is the need for continuous promotive and preventive interventions through nutrition education, increased physical activity, and routine health screenings to support employee health and productivity.